Wideband antennas on glass reinforced epoxy materials. (2021) - Sakthisudhan, K.; Bommi, R.M.; Sankar Ganesh, S.; Nandhakumar, S.; SenthilKumar, R.
Abstract: The wideband antennas have presented in this paper. The proposed antennas have a tunable, able to provide the multiband applications; which also offered the various modern wireless communication systems. It consists of two different shapes of (EF and ΨU ) conductive strips; stack on Epoxy based composite substrate in the array pattern. It has offered the resonant of 4.87 GHz and 5.42 GHz, with Fractional Bandwidth (FBW) of 24.64% and 23.33% respectively. These proposed antennas have a compact dimensional of 18.64x17.92x1 mm 2 . Hence, these prototypes have validated with respective wideband frequencies of the measurement analysis. These proposed antennas have effectively offered the Ultra Wide-Band (UWB) bands of operation, which includes the Industry, Scientific and Medical applications.